2019
DOI: 10.1016/j.ijproman.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

25 years of ‘sustainable projects’. What we know and what the literature says

Abstract: Last few years have seen a huge increase of publications at the intersection of project management and sustainability. Nevertheless, this field has become increasingly fragmented undermining a steady and consistent development. Aiming at balancing tensions between authors' attempts for more 'integration' and the trajectories toward 'fragmentation, we employed an extensive, systematic literature review of 770 publications from the period 1993 to 2017. Therefore, this review offers guidance to scholars less fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 89 publications
3
132
0
4
Order By: Relevance
“…Several authors (For example Silvius et al, 2012;Marcelino-Sádaba et al, 2015;Silvius, 2015;Huemann & Silvius, 2017) suggest that consideration of sustainability should be integrated into the processes and practices of project management, and sustainability is considered a new 'school of thought' in project management (Silvius, 2017). This approach, often labelled 'Sustainable Project Management' (SPM), is gaining traction in studies and publications (Silvius & Schipper, 2014;Aarseth et al, 2017;Armenia et al, 2019;Sabini et al, 2019), and SPM is identified as one of the most important global project management trends today (Alvarez-Dionisi et al, 2016).…”
Section: Introducuction Of the Problemmentioning
confidence: 99%
“…Several authors (For example Silvius et al, 2012;Marcelino-Sádaba et al, 2015;Silvius, 2015;Huemann & Silvius, 2017) suggest that consideration of sustainability should be integrated into the processes and practices of project management, and sustainability is considered a new 'school of thought' in project management (Silvius, 2017). This approach, often labelled 'Sustainable Project Management' (SPM), is gaining traction in studies and publications (Silvius & Schipper, 2014;Aarseth et al, 2017;Armenia et al, 2019;Sabini et al, 2019), and SPM is identified as one of the most important global project management trends today (Alvarez-Dionisi et al, 2016).…”
Section: Introducuction Of the Problemmentioning
confidence: 99%
“…In academia, the concept of SPM is viewed as a novel theme that accommodates different multifaceted dimensions from the domains of project management and sustainable development. While the scope of project management is well developed in both philosophy and application, the definition of SPM is in evolutionary stage where its organizational implications are yet to be clarified and understood [18,26] The prevailing SPM models tend to vary in their approach, but usually aim to represent the core sustainability dimensions with varying coverage of the environment, inter-generational equity and compliance beyond regulation [13]. In addition, the core concept of SPM in the construction industry covers the themes like lesser utilization of natural resources [27], due diligence towards project externalities [28] and conservation of human (as well as ecological) capital [29].…”
Section: Sustainable Project Managementmentioning
confidence: 99%
“…However, the extant literature offers limited insights on the integration perspective and more empirical evidence is, therefore, needed to explore the implications of SPM, studying it juxtaposed with well-grounded theoretical frameworks. A review of the literature published by leading authors in the field of SPM highlights the fact that few studies, till date, have actually attempted to explore the construct of SPM using framework-based quantitative designs [13,16,61]. Instead, the predominant majority of these studies include a qualitative case study method or systematic literature reviews.…”
Section: Measuring Spm As Second-order Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…The weaknesses of evaluation based on cash flows, both repeatable processes and unique projects, although seem natural, should be replaced by multi-aspect evaluation systems, methods and tools used to compare the desired effects and inputs, and reflect their diversity, multiplicity and complexity consistent with concepts of: Triple Bottom Line (TBL), Corporate Social Responsibility (CSR) and Sustainable Project Management (Sabini et al, 2019). An overview of research related to the field of sustainability and project management is presented in Toledo et al (2019).…”
Section: Introductionmentioning
confidence: 99%